Earnings Management, Buyout Group Reputation and Post-offering Long-Run Stock Performance of Reverse LBOs - ZHOU, Teng Yinzi (Institutional Knowledge at Singapore Management University, 2010)
This paper examines earnings management of private equity-backed IPOs around security offerings in a comprehensive sample of Reverse LBOs between 1981 and 2006. These RLBO companies are found to have positive level of discretionary current accruals (DCAs) at a much smaller magnitude compared to other IPOs. Buyout group's size is negatively related with the level of DCAs, suggesting that PE reputation mitigates accounting manipulations. Furthermore, PE reputation rather than earnings management can explain post-offering performance of RLBO companies.